Quantitative molecular profiling of biomarkers for pancreatic cancer with functionalized quantum dots - Lee, Kwan Hyi; Galloway, Justin F.; Park, Jeaho; Dvoracek, Charlene M.; Dallas, Matthew; Konstantopoulos, Konstaninos; Maitra, Anirban; Searson, Peter C. (ELSEVIER, 2012)
Applications in nanomedicine, such as diagnostics and targeted therapeutics, rely on the detection and targeting of membrane biomarkers. In this article we demonstrate absolute quantitative profiling, spatial mapping, and multiplexing of cancer biomarkers using functionalized quantum dots (QDs). We demonstrate highly selective targeting molecular markers for pancreatic cancer with extremely low levels of nonspecific binding. We confirm that we have saturated all biomarkers on the cell surface, and, in conjunction with control experiments, extract absolute quantitative values for the biomarker density in terms of the number of molecules per square micron on the cell surface. We show that we can obtain quantitative spatial information of biomarker distribution on a single cell, important because tumors' cell populations are inherently heterogeneous. We validate our quantitative measurements (number of molecules per square micron) using flow cytometry and demonstrate multiplexed quantitative profiling using color-coded QDs. From the Clinical Editor: This paper demonstrates a nice example for quantum dot-based molecular targeting of pancreatic cancer cells for advanced high sensitivity diagnostics and potential future selective therapeutic purposes. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: TARGET; EXPRESSION; MESOTHELIN; CLAUDIN-4